Para Politikası ve Konut Fiyatları İlişkisi: Türkiye Ekonomisi için Ampirik Bir Analiz - Darıcı, Burak (Muş Alparslan Üniversitesi, 2018)
Buçalışmada Türkiye ekonomisi için 2010-2016 yılları arası aylık verilerle parapolitikasının konut fiyatları üzerindeki etkisi ARDL modeli aracılığıylaaraştırılmaktadır. Elde edilen bulgular, genişletici para politikasının konutfiyatlarını artırıcı yönde bir baskı yarattığını ortaya koymaktadır. Bu sonucagöre, genişletici para politikasının bankaların kredi verme imkânlarınıarttırması, toplam talep üzerinde pozitif bir etki yaratmaktadır. Bu süreçtekarlılık oranlarını arttırmak için bankaların daha fazla kredi yaratması sonucuartan konut fiyatlarına bağlı balon oluşması durumunda finansal istikrarsızlıkoluşabilmektedir. TCMB’nin genişletici para politikası uygulamalarında proaktifdavranarak varlık fiyatlarında oluşabilecek bu balonu izlemesi ve önlemesigerekmektedir.

In this study, the effects of monetary policy onhousing prices are being investigated with monthly data for the period between2010 and 2016 by using the ARDL model. The findings obtained show thatexpansionary monetary policy creates a pressure to increase housing prices.This result implies that increasing lending opportunities of banks of theexpansionary monetary policy has a positive impact on aggregate demand.Occurrences of bubbles due to increases in housing prices, which are caused bycreation of more loans by banks to increase profitability ratio (rate), maycreate financial instability. CBRT should monitor and prevent the potentialbubbles in asset prices via proactive actions in its implementation ofexpansionary monetary policy.
The Relationship between Monetary Policy and Housing Prices: An Empirical Analysis for Turkish Economy
anemon
Keywords: Varlık Fiyat Balonları; Para Politikası; Konut Fiyat Endeksi; Türkiye Ekonomisi; ARDL Modeli; Asset Price Bubbles; Monetary Policy; House Price Index; Turkish Ekonomy; ARDL Model